2024
DOI: 10.26599/fshw.2022.9250069
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite acetyl- L-carnitine participates in Bifidobacterium animalis F1-7 to ameliorate atherosclerotic inflammation by downregulating theTLR4/NF-κB pathway

Abstract: This study aimed to explore the effect of Bif. Animalis F1-7 on the improvement of atherosclerotic inflammation. Arteriosclerosis model ApoE -/mice were orally administered with Bif. Animalis F1-7 for 12 weeks. The probiotic intervention reduced the plaque areas in aorta and the accumulation of macrophages, and downregulated the expression of toll-like receptor 4 (TLR4)/nuclear factor-κB (NFκB) pathway to reduce the levels of inflammatory factors. The widely-targeted metabolomics analysis showed that acetyl-L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Lucas, S. et al reported the effect of propionic acid and other SCFAs on bone mass, they found that it could inhibit osteoclast differentiation and reduce bone resorption . Meanwhile, Combining the study and our findings, SCFAs were also associated with the production of inflammatory factors . Therefore, we speculated that SCFAs might improve osteoclast differentiation by regulating the inflammatory factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lucas, S. et al reported the effect of propionic acid and other SCFAs on bone mass, they found that it could inhibit osteoclast differentiation and reduce bone resorption . Meanwhile, Combining the study and our findings, SCFAs were also associated with the production of inflammatory factors . Therefore, we speculated that SCFAs might improve osteoclast differentiation by regulating the inflammatory factors.…”
Section: Discussionsupporting
confidence: 93%
“…26 Meanwhile, Combining the study and our findings, SCFAs were also associated with the production of inflammatory factors. 52 Therefore, we speculated that SCFAs might improve osteoclast differentiation by regulating the inflammatory factors. Furthermore, SCFAs improved the solubility of minerals in the gut by reducing the intestinal pH, thereby making calcium more easily absorbed by the body and improving bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, 18,19 B. bifidum FL228.1 and B. animalis F1–7 have shown excellent inhibitory effects on intestinal inflammation and are stored in the Functional Dairy and Probiotic Engineering Laboratory of Ocean University of China. B. bifidum FL228.1 and B. animalis F1–7 were cultured twice in de Man, Rogosa, and Sharpe (MRS) broth before being incubated anaerobically at 37 °C for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…B. bifidum FL228.1, FL276.1 and ZL.1 were cultured twice in de Man, Rogosa, and Sharpe (MRS) broth before being incubated anaerobically at 37 °C for 48 h. To collect the bacteria, the strain fermentation broth was centrifuged (4 °C, 8000 rpm, 5 min), washed twice with pre-cooled sterile phosphate-buffered saline (PBS), then re-suspended in sterile PBS, and the concentration of bacteria was adjusted to 5 × 10 8 CFU mL −1 using the colony counting method for in vivo experiments. 24…”
Section: Preparation Of the Bacterial Suspensionmentioning
confidence: 99%